Peran Kepala Madrasah dalam Meningkatkan Kualitas Pendidikan - Muhammad Romadlon Habibullah; Abdul Basir (Pascasarjana Universitas Qomaruddin, 2023)
The importance of education as the main foundation in developing human potential has a significant impact on the progress of a country. The future of a nation really depends on the quality of education implemented in the current era. High quality education can be realized if educational institutions are serious about paying attention to the quality of education itself. The decline in the quality of education in Indonesia occurs due to a greater focus on the input and process aspects of education. One of the contributing factors is the lack of quality, competence and professionalism of the majority of Madrasah Heads. Therefore, an important step to improve the quality of education is to empower the role of Madrasah Heads. Madrasah principals have a central role as drivers of productivity in managing resources in schools, especially for teachers and school staff. The success of school activities as a whole depends greatly on the quality of leadership of the Madrasah Principal. Therefore, it is necessary to implement educational leadership by the Madrasah Head. This research, which is qualitative in nature, aims to understand the role of Madrasah Heads in improving the quality of education at MA AL-AZHAR Banjarwati Paciran Lamongan. The research results show that the role of madrasa heads in improving the quality of education is carried out through several efforts, such as developing curriculum administration, facilities and infrastructure, human resources, and community participation. Supporting factors involve togetherness in managing the curriculum, adequate facilities and infrastructure, and the success of professional teachers. While inhibiting factors involve differences in students' psychological abilities and souls, low community participation, lack of funding, and lack of teacher enthusiasm.